Plan de negocio para la exportación de sombreros a base de fibra de banano - Orrala Carlier, Norma Estefanía (2021)
In this project, the objective is develop a business plan for the creation of a company that produces and exports hats based on banana fiber. For it identified the problem to next development, the respective justification and set up the objectives. After this, there is the theoretical section with the bibliographic sources used for the development of this project, the history, details and characteristics of the composition of the hat, concepts of vegetable fiber, production information and commercialization of bananas nationally and internationally, and the important theoretical elements that are required to execute the business plan for the composition of the company.....